(untitled) (American Journal of Technology and Applied Sciences, 2023)
The article examines the study of physical and chemical properties of secondary gases emitted from chemical industry enterprises and solving the problems of gas disposal based on their analysis. In the article, the theoretical justification of the hydrodynamic forces acting on the secondary gas in the chemical industry and the efficiency of the device are developed.